2014
DOI: 10.4269/ajtmh.13-0554
|View full text |Cite
|
Sign up to set email alerts
|

The Peculiar Epidemiology of Dracunculiasis in Chad

Abstract: Dracunculiasis was rediscovered in Chad in 2010 after an apparent absence of 10 years. In April 2012 active village-based surveillance was initiated to determine where, when, and how transmission of the disease was occurring, and to implement interventions to interrupt it. The current epidemiologic pattern of the disease in Chad is unlike that seen previously in Chad or other endemic countries, i.e., no clustering of cases by village or association with a common water source, the average number of worms per pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
183
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(189 citation statements)
references
References 16 publications
4
183
0
2
Order By: Relevance
“…We used standard procedures, as previously described ( 1 ), to examine muscle and viscera of 88 frogs from the study area; the frogs, which were of several sizes and species (i.e., Ranidae, Pipidae, Phrynobatrachidae, Bufonidae), were collected by local villagers and fishermen. In brief, the viscera was removed and placed in water for at least 1 h before being examined by microscope for motile nematode larvae.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We used standard procedures, as previously described ( 1 ), to examine muscle and viscera of 88 frogs from the study area; the frogs, which were of several sizes and species (i.e., Ranidae, Pipidae, Phrynobatrachidae, Bufonidae), were collected by local villagers and fishermen. In brief, the viscera was removed and placed in water for at least 1 h before being examined by microscope for motile nematode larvae.…”
Section: The Studymentioning
confidence: 99%
“…The peculiar epidemiology of Dracunculus medinensis (Guinea worm), the causative agent of dracunculiasis (Guinea worm disease), in Chad has led to speculation that a paratenic host is involved in the life cycle, most likely an animal with an aquatic stage that would feed upon copepods and harbor the infection for subsequent transmission to a human or dog definitive host ( 1 ). Recent experiments demonstrated that D. medinensis worms, like the closely related parasite D. insignis , could utilize green frog ( Lithobates clamitans ) tadpoles as a paratenic host ( 2 ).…”
mentioning
confidence: 99%
“…Finally, these results also suggest that a more extensive examination of tadpoles and frogs in Chad is warranted. Although a small number (n = 28) of ranid frogs from Chad were previously examined for Dracunculus larvae and all were negative ( 2 ), sample sizes were low. Because natural infections of tadpoles or frogs have not been documented for either D. medinensis or D. insignis, the prevalence of natural infections is unknown; therefore, larger numbers of wild-caught frogs should be examined in future efforts.…”
Section: Discussionmentioning
confidence: 99%
“…However, in 2013, several unusual epidemiologic findings were noted in Chad, including absence of disease outbreaks associated with sources of drinking water common to many residents year-to-year in affected villages and a relatively common infection of domestic dogs with Guinea worms genetically indistinguishable from those from human cases. This finding led to the hypothesis that an aquatic paratenic host (an intermediate host that serves as transport host for parasite larvae) was involved in the transmission of Dracunculus medinensis in Chad ( 2 ). Since 2013, the sporadic pattern of human cases in Chad has continued, the number of infections in dogs has continued to increase, and the presence of a paratenic host in the transmission cycle seems more likely.…”
mentioning
confidence: 99%
“…However, they still threaten the lives of more than 1 billion people worldwide [3]. Moreover, NTD outbreaks associated with previously unrecognized biological or epidemiological features were recently reported [4,5].…”
mentioning
confidence: 98%